Religious Thoughts and Practice of the Kaum Menak: Strengthening Traditional Power - Nina Herlina Lubis (Studia Islamika, 2003)
In this article, discussion will be directed to delineating the history of the kaum menak, placing emphasis on their religious thoughts and practices. Having been political elites, it is important to emphasize that the kaum menak had to adapt to changing circumstances, both in terms of religion and politics. The religious life of kaum menak had social and political significance, and owing to their position within the society, it formed an important part of their existence. As will be made appearent explained in this article, the religious thoughts and practices of the kaum menak functioned as sources of their authority and were closely related to their efforts of maintaining political power within society.DOI: 10.15408/sdi.v10i2.629